PENERAPAN PROGRAM MARKET DAY UNTUK MENINGKATKAN KREATIVITAS DAN JIWA KEWIRAUSAHAAN SISWA DI SDN UJUNGRUSI 04 - Indri Astuti, Retno; Indah Fujiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT This study aims to understand the Market Day program's role in enhancing creativity and entrepreneurial spirit among students at SD Negeri Ujungrusi 04 in Tegal Regency. This research utilizes a descriptive qualitative method. For data collection, the researcher used observation, documentation, and in-depth interviews with subjects designated as informants in this study. The results of the research conducted by the researcher indicate that (1) The Market Day program at SD Negeri Ujungrusi 04 is an entrepreneurial skills education program patterned on buying and selling activities conducted at the school. The primary target is students, with the main goal of enhancing their creativity and entrepreneurial spirit. The stages of implementing Market Day include planning, production, buying and selling, and evaluation. (2) The entrepreneurial spirit among the students at SD Negeri Ujungrusi 04 is observed to be very good and positive. The entrepreneurial traits that have developed in the students include discipline, independence, responsibility, communication, creativity, innovation, risk-taking, and good teamwork. (3) In practice, the Market Day at SD Negeri Ujungrusi 04 takes the form of a buying and selling activity conducted in the school yard, involving the entire school community, including students (production and distribution), teachers (consumers), school staff (consumers), and also external parties such as parents visiting the school who act as consumers. Keywords: Market Day, Creativity, Entrepreneurial Spirit